Mental workload as personal data: designing a cognitive activity tracker - Wilson, Max L.; Sharon, Natalia; Maior, Horia A.; Midha, Serena; Craven, Michael P.; Sharples, Sarah (2018)
Research continues to correlate physical signals with mental activity, as opposed to physical activity, with physiological sensors. Further, with the proliferation of wearable technology, it seems imminent that our smart watches can soon keep track of our mental activity as well as our physical activity. Our research is working towards accurately measuring Mental Workload ‘in the wild’ using physiological sensors. While we work towards that goal, however, we have begun to explore the design aspects of representing personal cognitive data to users; analogous to a step counter for physical activity. We present the results of diary studies, focus groups, and prototyping exercises to identify design considerations for future cognitive activity trackers.